2019
DOI: 10.3390/scipharm87020008
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative and Quantitative Analysis of Different Rhodiola rosea Rhizome Extracts by UHPLC-DAD-ESI-MSn

Abstract: Rhodiola rosea has been used in folk medicine as ethanolic macerates for a long time. This study aims to provide a quantitative and qualitative analysis and comparison of different ethanolic Rhodiola rosea rhizome macerates (35%, 70%, and 96% v/v) and accelerated solvent extraction (ASE) extracts prepared with 85% methanol, in order to shed light on the effectivity of different extraction methods. Extract samples were analyzed by UHPLC-DAD-ESI-MS n on a ZORBAX SB-C18 column (100 × 2.1 mm, 1.8 µm) with a mobile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 29 publications
2
23
0
Order By: Relevance
“…On the other hand, Zomborszki et al (2019) reported that different drying methods did not affect the content of the bioactive compounds of R. rosea [ 59 ]. Our results supported the first hypothesis that freeze-drying of plant material before the extraction at low temperatures prevents degradation of bioactive compounds and ensures a high yield of bioactive compounds [ 58 , 60 , 61 , 62 ]. Long-term vegetative propagation and high genetic diversity [ 21 ] of R. rosea , together with the freeze-drying method, may explain the high content of the bioactive compounds observed in the current study.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…On the other hand, Zomborszki et al (2019) reported that different drying methods did not affect the content of the bioactive compounds of R. rosea [ 59 ]. Our results supported the first hypothesis that freeze-drying of plant material before the extraction at low temperatures prevents degradation of bioactive compounds and ensures a high yield of bioactive compounds [ 58 , 60 , 61 , 62 ]. Long-term vegetative propagation and high genetic diversity [ 21 ] of R. rosea , together with the freeze-drying method, may explain the high content of the bioactive compounds observed in the current study.…”
Section: Discussionsupporting
confidence: 87%
“…The various methods used to dry and extract the bioactive compounds of R. rosea have a large impact on the yield of phenyletanes and phenylpropanoids [ 36 , 58 ]. On the other hand, Zomborszki et al (2019) reported that different drying methods did not affect the content of the bioactive compounds of R. rosea [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…In Figure 1 the proton spectra of the analysed Rhodiola plants and products in the aromatic region, where significant metabolite variations were observed, are presented. Salidroside and p ‐tyrosol have been previously reported in R. rosea , R. kirilowii , 20–22,27,47,48 R. crenulata and other Rhodiola species 24,25,49 . However, rosavins accumulation is restricted among the Rhodiola species and has been reported in R. rosea , 20,22,27 R. quadrifida and R. sachalinensis 33,35 .…”
Section: Resultsmentioning
confidence: 96%
“…The treatment that showed the greatest C. jejuni QS reduction was the S. rosea (roseroot) ethanolic extract (E8), and this also had the greatest effect on C. jejuni motility and was among the best in terms of reduced invasion of INT407 cells and adhesion to polystyrene surfaces by C. jejuni. The roseroot extract is composed of different cyanogenic glycosides, phenylethanoids, procyanidin and catechin derivatives, phenylpropanoids, monoterpene alcohols, and flavonoids [29], and isolated compounds of this extract should be considered in the search for new anti-QS compounds against C. jejuni. Also, rosmarinic acid (P2) was among the weakest in terms of effects on C. jejuni QS, motility, and adhesion to polystyrene surfaces.…”
Section: Discussionmentioning
confidence: 99%
“…The post-distillation material was prepared with the same protocol but used after the distillation process. Finally, extracts were dried fully using a nitrogen flow and stored at −20 • C. The roseroot (E8) was provided by Bucar F. (Department of Pharmacognosy, Institute of Pharmaceutical Sciences, University of Graz, Graz, Austria) and was prepared as described by Alperth et al [29].…”
Section: Extract Preparationmentioning
confidence: 99%